Perancangan Sistem Inventory dan Penjualan Berbasis Microsoft Access pada UMKM Koko Tua - Isnaini Nuzula Agustin; Andryanto (Lembaga Dongan Dosen, 2023)
Koko Tua is one of the Micro, Small and Medium Enterprises (MSMEs) in Batam City which operates in the sales and service sector of watches and also trades watches. While this business has been established for 4 years, currently Koko Tua records their sales using manual techniques, namely using notebooks and there is no recording of goods or inventory. The aim of this activity is to design a purchasing, sales and inventory recording system that is accurate, simple and easy to use in recording Koko Tua MSME transactions in their daily operational activities. The collection techniques used in implementing system design include interviews, observation and documentation. The results of this activity show that the designed purchase, sales and inventory recording system has proven to be accurate, simple and easy to use in recording Koko Tua MSME transactions. The recording system implemented is expected to be able to support the process of recording transactions and compiling transaction reports as well as serving as a warning system in controlling store inventory availability.